Prevalence of Depression in the Diabetic Population and its Influence on Glycaemic Profile: A Prospective Interventional Study - Karimulla, Shaik (Indian Journal of Pharmaceutical Education and Research, 2018)
Objectives: The study aims to determine the prevalence of depression in the diabetic population and its influence on glycaemic profile. Materials and Methods: A prospective interventional study was conducted at Narayana Medical College and Hospital, Nellore, Andhra Pradesh, India. This study included 300 patients diagnosed with Type 2 Diabetes (T2D) and exhibiting depression with a PHQ-9 score >5. Depression levels were assessed before and after the intervention using validated measures. A chi-square test was used to analyze the changes in depression status, while a t-test was employed to evaluate the effect of the intervention on glycaemic control. The reduction in depression levels following the intervention was also reported. Results: After a 4-month psychotherapeutic intervention, significant improvements were observed in both depression severity and glycaemic control. The percentage of patients without depression increased from 65.10% to 74.84%, while those with mild, moderate, and severe depression decreased to 34.40%, 29.30%, and 8.40%, respectively, indicating a substantial reduction in depression levels. Glycaemic control also showed significant improvements, with HbA1c levels decreasing from 9.2±1.5% to 7.3±1.2%, and similar improvements were observed in Fasting Blood Sugar (FBS) and Postprandial Blood Sugar (PPBS) levels (p<0.01). Conclusion: The 4-month psychotherapeutic intervention significantly reduced depression levels and improved glycaemic control in patients with Type 2 Diabetes. These findings highlight the importance of addressing both mental health and glycaemic management for better overall outcomes. Integrated treatment approaches may enhance the quality of life for patients with comorbid diabetes and depression.
Keywords: Diabetes; Depression; Glycaemic profile; Intervention